Camera (Webcam) Monitoring Application for Mobile Device Based on Android - Taufiqurrahman Taufiqurrahman; Muhammad Akid Musyafa; Elvanisa Ayu Muhsina; Muhammad Taufiq Nuruzzaman (Faculty of Science and Technology, UIN Sunan Kalijaga Yogyakarta, 2014)
Security system using camera for monitoring usually called CCTV are in common use lately. The goal is to do monitoring surroundings from another place directly and easily. But it spend a lot of money for applying the system, according to hardware also installation service. And the system usually just doing offline monitoring at the local area. On the other side, improvement of technologies for mobile devices are very rapid. Many people using it just like smartphone and tablet. And also availability of cheap internet connection make those devices become urgently to be owned, because the necessity of accurate information and communications are important to support their daily activities in advance of information technologies era. To reduce the problem, it is necessary to build mobile monitoring application which can accessed from another place where ever and whenever by using internet connections such Wi-Fi or even from mobile packet data.Mobile Monitoring application was built on client-server model. On the server side had a desktop application which it developed by Delphi programming language. The desktop application have features, there were such motion detector, record on motion and capture image. Meanwhile, mobile application was on the client side. This mobile application was developed by java programming language for android mobile device, which it did remote toward desktop application located inside webserver. Mobile application acts as a direct interface for user on monitoring situation using internet network connections. This research had more focused on discussing about Android Mobile Monitoring application and how it worked.This Android Mobile Monitoring application capable to do streaming video using RTSP protocol, recording video, record on motion capturing image, browsing image and video databases also showing alert notifications when motions were detected.